Raja Bandung Banana (Musa paradisiacaL.cv Raja Bandung) Prevents Increased Systolic Blood Pressure in Rats Given Acute Stress Test - Dina Septari Anindyah; Arta Farmawati (Intelektual Pustaka Media Utama, 2015)
The relationships between stress and hypertension have been evaluated. Heightened blood pressure (BP) reactions to acute stress have been implicated in cardiovascular disease’s development. Consumption of fruit or vegetables lowering BP. This study aimed to evaluate the effect of Raja Bandung Banana (Musa paradisiacaL. cv Raja Bandung) on blood pressure after acute restraint stress and forced swim test.Twenty male Sprague dawley rats were divided into 4 groups (A,B,C,D) and adapted for 3 days. At 4th day, groups were administered 2 g/200gBw AIN-93M, then exposed to acute restraint (1hour), except group A. After restraint, A&B received water, C received diazepam 0,5mg/kgBW, and D received banana 2,52 g/200gBW. One hour later, the forced swim test was carried out (45 minutes). Blood pressure was measured 1 hour after swim. Result showed,mean of blood pressure significantly increased after treatment (p<0,01) all groups. But, the increasing of blood pressure in C and D group was lower than unrestraint (A) and control (B) group. There was significant difference of blood pressure between control (A&B) and intervention group (C&D), but no significant difference between C and D. Thisresults indicate that Raja Bandung Banana can prevent increased blood pressure on acute stress condition as effective as diazepam.